Associations between GJB2, Mitochondrial 12S rRNA, SLC26A4 Mutations, and Hearing Loss among Three Ethnicities. (2nd April 2014) - Du, Wan; Wang, Qiuju; Zhu, Yiming; Wang, Yanli; Guo, Yufen
Abstract : The epidemiological researches show that the mutations of GJB2, mitochondrial 12S rRNA, and SLC26A4 genes have played an important role in the hearing loss. This study aims to investigate the mutation spectrum of GJB2, mitochondrial 12S rRNA, and SLC26A4 genes of Han Chinese, Hui people, and Uyghur ethnicities in sensorineural hearing loss (SNHL) patients in northwest of China. Mutational analyses in the three genes were brought by direct sequencing and each fragment was analyzed using an ABI 3730 DNA Sequencer. The mutation frequencies for the three HL causative genes were 34.05% in Han Chinese participants, 27.47% in Hui people, and 14.44% in Uyghur participants, respectively. The prevalence of GJB2 mutations was 13.7%, 11.4%, and 11.4% in Han Chinese, Hui people, and Uyghur participants (χ 2 = 10.2, P < 0.05 ), respectively. The prevalence of mtDNA 12S rRNA A1555G homozygous mutations was 6.05%, 3.27%, and 1.44% in Han Chinese, Hui people, and Uyghur participants (χ 2 = 13.9, P < 0.05 ), respectively. The prevalence of SLC26A4 mutations was 14.3%, 12.8%, and 1.6% in Han Chinese, Hui people, and Uyghur participants, respectively. In summary, we find that Uyghur and Hui SNHL individuals vary significantly from Han Chinese patients in three causative HL genes' mutational spectrum, especially for Uyghur.